Relationship of perceived environmental characteristics to self-efficacy and leisure time physical activity among Asian immigrants in the U.S. - Jaehyun Kim; Andrew J. Mowen; Benjamin D. Hickerson; Alan Graefe; Melissa Bopp (Tabriz University of Medical Sciences, 2020)
Background: Given the high prevalence of physical inactivity among Asian immigrants and its potential negative effects on health, more attention should be paid to identifying factors that might affect their participation in leisure time physician activity (LTPA). This study examined how perceived environmental characteristics are related to self-efficacy and LTPA among Asian immigrants in the United States. Methods: This cross-sectional study collected data from an on-line survey administered through Qualtrics, a web-based survey software company. In the data analysis, 512 Asian immigrants were included. As independent variables, we assessed perceived environmental characteristics with regard to the perceived accessibility of LTPA-related sites and neighborhood quality. As mediating and outcome variables, we measured self-efficacy and LTPA, respectively. Using AMOS version 22, a path analysis was conducted to measure model fit. Results: The perceived accessibility of the LTPA-related sites (b = 0.10, P = 0.04) and self-efficacy(b = 0.26, P = 0.001) were positively related to LTPA. Perceived neighborhood quality (b = 0.11,P = 0.012 was positively associated with self-efficacy, yet not directly associated with LTPA. Self-efficacy mediated the relationship between the perceived accessibility of LTPA-related sites and LTPA (estimate=0.036, 95% CI=0.015-0.067, P = 0.003). Conclusion: This study suggests that perceiving easy access to LTPA-related sites and living in quality neighborhoods can encourage people to participate in LTPA more often by increasing their self-efficacy toward LTPA. These findings highlight a need for public infrastructural investments to improve accessibility to LTPA-related resources and neighborhood quality, which can potentially increase self-efficacy and promote LTPA among Asian immigrants.